Design and experiment of noncontact eddy current damping module in air bearing–guided linear motion system. (August 2019) - Sung, Eunho; Seo, Chang-hoon; Song, Hyunmin; Choi, Byungjoo; Jeon, Yongho; Choi, Young-Man; Kim, Kihyun; Lee, Moon G
As a method for reducing the friction of high-precision system, air bearings have been widely used for various industrial applications. However, their small damping leads to poor in-position stability and therefore systems are susceptible to residual vibration and disturbance. In this study, a linear motion stage which is guided by air bearing for a noncontact eddy current damping module is proposed. The eddy current damping module consists of a Halbach array of permanent magnets and a fixed conductor plate. An eddy current is generated in the conductor in the direction opposing the change in the magnetic field when the magnets move, after which the resistivity in the conductor dissipates the kinetic energy of the moving part; therefore, the module has a damping effect without contact and system is shown good in-position stability. In order to specify the damping effect, the motion of the moving part was experimentally analyzed. The step response confirmed that the eddy current damping module can improve the performance of the positioning system: the settling time decreased by 36.8% and the resolution improved by 59.4%. These improvements verify that eddy current damping is a suitable method for application in precision industries.